Chemical analysis of the antioxidants from the aerial parts of wild Polygonum equisetiforme from Tunisia. (June 2019) - Mahmoudi, Maher; Boughalleb, Fayçal; Mabrouk, Mahmoud; Tlili, Nizar; Potter, Daniel; Abdellaoui, Raoudha; Nasri, Nizar
Abstract: The antioxidant capacities of 11 populations of P. equisetiforme collected from the Saharan, arid, and semi-arid bioclimatic zones in Tunisia were investigated. Total phenolic content varied from 31 ± 5 to 113 ± 4 mg GAE/g dw. Flavonoid content varied from 29 ± 2 to 130 ± 10 mg QRE/g dw and condensed tannins ranged between 8 ± 1 and 33 ± 2 mg CTE/g dw. P. equisetiforme showed a high antioxidant potential, with the total antioxidant capacity varying from 10 ± 2 to 71 ± 3 mg GAE/g dw. The DPPH scavenging activity ranged from 12 ± 1 to 51 ± 6 mM TRE/g dw and the EC50 of reducing power ranged between 68 ± 5 and 210 ± 20 μg/mL. Plants collected from the Saharan climate showed the highest phytochemical and antioxidant activity. LC–ESI-MS analysis allowed identification of 19 compounds, of which quinic acid, gallic acid, (+)-catechin, epicatechin, quercetin-3-O-galactoside, quercetin-3-O-rhamnoside, and cirsiliol were identified as major compounds. High quantitative and qualitative variability in the phenolic acid and flavonoid fractions between the studied populations were observed. Overall, P. equisetiforme could be considered as a prospective source of useful natural antioxidants.